2023
DOI: 10.3390/ijms24065123
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Mining Approach to Identify NF-kB-Responsive microRNAs in Tissues Involved in Inflammatory Processes: Potential Relevance in Age-Related Diseases

Abstract: The nuclear factor NF-kB is the master transcription factor in the inflammatory process by modulating the expression of pro-inflammatory genes. However, an additional level of complexity is the ability to promote the transcriptional activation of post-transcriptional modulators of gene expression as non-coding RNA (i.e., miRNAs). While NF-kB’s role in inflammation-associated gene expression has been extensively investigated, the interplay between NF-kB and genes coding for miRNAs still deserves investigation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 135 publications
0
0
0
Order By: Relevance
“…One of the most well studied inducers of senescence in NP cells is TNFα [9,21], however the mechanism through which TNFα induces senescence is still not fully delineated. Studies have implicated PI3K-Akt [21], pSTAT3 [22], miRNAs [23], and SIRT [24] as potential signaling mechanisms. Recent work has demonstrated that TNFα induced senescent NP cells secrete soluble factors that are capable of inducing senescence in healthy NP cells [22], however the effect of these soluble factors on AF cells have not been assessed [25].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most well studied inducers of senescence in NP cells is TNFα [9,21], however the mechanism through which TNFα induces senescence is still not fully delineated. Studies have implicated PI3K-Akt [21], pSTAT3 [22], miRNAs [23], and SIRT [24] as potential signaling mechanisms. Recent work has demonstrated that TNFα induced senescent NP cells secrete soluble factors that are capable of inducing senescence in healthy NP cells [22], however the effect of these soluble factors on AF cells have not been assessed [25].…”
Section: Introductionmentioning
confidence: 99%